2006
DOI: 10.1089/aid.2006.22.301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of HTLV-II Subtype B Among an Urban Population Living in South Brazil

Abstract: Human T cell lymphotropic virus type II (HTLV-II) is a deltaretrovirus endemic in Indian populations living in Central and South America, among Pygmies tribes from Central Africa, and epidemic among injecting drug users (IDUs) in the United States, Europe, Southeast Asia, and South America. To date only the HTLV-IIa subtype has been demonstrated among Brazilians (Amazon basin Indians, blood donors, and IDUs). We analyzed HTLV-II isolates from 12 individuals living in the urban area of Porto Alegre, Southern Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
11
1
4
Order By: Relevance
“…Consistent with this finding, the HTLV-2b subtype has been found in the state of Rio Grande do Sul in Brazil, 20 bordering countries where the HTLV-2b subtype prevails. We could speculate that with the commercial agreement of Mercosul, the increasing population flux across borders warrants monitoring this viral subtype in the country.…”
Section: Figsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with this finding, the HTLV-2b subtype has been found in the state of Rio Grande do Sul in Brazil, 20 bordering countries where the HTLV-2b subtype prevails. We could speculate that with the commercial agreement of Mercosul, the increasing population flux across borders warrants monitoring this viral subtype in the country.…”
Section: Figsupporting
confidence: 77%
“…7 Therefore, HTLV-2 molecular characterization worldwide disclosed four HTLV subtypes: HTLV-2a and HTLV-2b, the most prevalent among IDUs from urban areas of the Americas and Europe and in the indigenous population of the Americas, and with sporadic distribution in Asia and Africa; the HTLV-2c variant detected in the indigenous population of the Brazilian Amazon and in IDUs from urban populations in Brazil; and the HTLV-2d detected in pygmy tribes in Africa. 13,[16][17][18][19][20][21] In 2010, we started the characterization of HTLV-2 isolates that circulate in HIV-coinfected individuals from southern Brazil using nucleotide sequence and restriction fragment length polymorphism (RFLP) analysis of the LTR region, and confirmed that all HTLV-2 strains belonging to the 2a subtype. Moreover, we observed an association of molecular variants and sexual risk factor and injecting drug use.…”
Section: Figmentioning
confidence: 99%
“…A presença deste subtipo no Brasil foi recentemente descrita entre doadores de sangue em Porto Alegre (RS), sendo atribuída à migração a partir da fronteira com a Argentina 25 .…”
Section: Discussionunclassified
“…The history of HTLV is a fascinating one regarding its possible origin in the African continent and its spread in different directions according to human migration routes [4], and the ARB is of paramount importance because of the presence of a specific strain of the virus that originated during human migration into the area and its further dissemination to other geographical areas in the country and abroad [36,51,[91][92][93][94][95][96][97].…”
Section: The Amazon Region Of Brazilmentioning
confidence: 99%